2021
DOI: 10.1177/1534735420983443
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Use of Two Brief Fatigue Screening Tools in Cancer Outpatient Clinics

Abstract: Purpose: Cancer fatigue guidelines recommend routine fatigue screening, with further assessment for people reporting moderate to severe fatigue. There is neither a gold-standard, nor a broadly accepted screening method, and knowledge about the impact of screening on care processes is limited. This study aimed to explore the feasibility of 2 fatigue screening methods and current clinical practice in cancer outpatient clinics. Methods: Hospital outpatients attending cancer clinics during 1 week completed a five-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Another study evaluated the ease of use of a Numerical Rating Scale (NRS) and a Fatigue Pictogram in cancer outpatient care. 15 Although the results of this study showed that both screening programmes are equally applicable in practice, it remains an open question which time points and time intervals are most appropriate for screening of CRF. The European Society for Medical Oncology-guidelines have no definite, strict recommendation but suggest a quantitative scale, such as an NRS ranging from 0 to 10 with a cut-off ≥4.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…Another study evaluated the ease of use of a Numerical Rating Scale (NRS) and a Fatigue Pictogram in cancer outpatient care. 15 Although the results of this study showed that both screening programmes are equally applicable in practice, it remains an open question which time points and time intervals are most appropriate for screening of CRF. The European Society for Medical Oncology-guidelines have no definite, strict recommendation but suggest a quantitative scale, such as an NRS ranging from 0 to 10 with a cut-off ≥4.…”
Section: Introductionmentioning
confidence: 79%
“…Here, it still remains unclear if the results are generalisable to other patients with cancer undergoing different treatments and if these assessment tools are feasible in clinical practice. Another study evaluated the ease of use of a Numerical Rating Scale (NRS) and a Fatigue Pictogram in cancer outpatient care 15. Although the results of this study showed that both screening programmes are equally applicable in practice, it remains an open question which time points and time intervals are most appropriate for screening of CRF.…”
Section: Introductionmentioning
confidence: 99%
“…The two questions that make up the Fatigue Pictogram were divided into Pictogram A for the first question and Pictogram B for the second question, being grouped and classified as follows: "not at all tired " for "no fatigue"; "a little bit tired" for "mild fatigue"; "somewhat tired" and "moderately tired" for "moderate fatigue"; "extremely tired" for "extreme fatigue". The second item was grouped as follows: "I can do everything I normally do" for "no fatigue"; "I can do almost everything I normally do" for "mild fatigue"; "I can do some the things I normally do" for "moderate fatigue"; and finally "I do what I have to do" and "I can do very little" for "severe fatigue" 12 .…”
Section: Variablesmentioning
confidence: 99%